Orff-Schulwerk approach and flow indicators in music education context: a preliminary study in Portugal - Cunha, João Cristiano (2011)
Extensive literature exists on Flow Theory. However there is a lack of published research investigating possible links between Orff-Schulwerk approach and Csikszentmihalyi’s concept of flow or optimal experience. Based on preliminary results from an ongoing research on Music / Music Pedagogy and (is links to) Musical Thought / Musical Cognition, the present paper aims to discuss the existence of optimal experiences / flow states boosted by Orff- Schulwerk approach activities / teaching music strategies in the context of Music Education in a Portuguese general public school (5th and 6th grades). Attempting to verify, analyze and understand these relationships, an empirical process was developed based on the Flow Theory - Optimal Experience (Csikszentmihalyi 1975, 1988, 1990) and consequently on FIMA - Flow Indicators in Musical Activity developed by Custodero (1998, 1999). Conventional flow methodology is adapted in order to define and to operacionalize cognitive strategies exhibited during Orff-Schulwerk approach activities in Music Eduction context. Results clearly validated this hipotesys and show how (and which) Orff-Schulwerk activities can provide children optimal experience /flow states in Music Education classes.